Answer:
D) y= 7/3 X -11/3
Explanation:
Using the point slope equation of a line expressed as
y-y0 =m(x-x0)
(x0,y0) is the point on the line
m is the slope
First let us get the slope of the line passing through (-4, 1) and (3, -2)
m = y2-y1/x2-x1
m = -2-1/3+4
m= -3/7
Since yh required line is peependicular to this line, then its slope will be;
M= -1/m
M = -1/(-3/7)
M = 7/3
Get the equation needed
Substitute m = 7/3 an the point (2,1) into the equation above
y - 1= 7/3(x-2)
y = 7x/3-14/3 +1
y= 7x/3 -11/3
Hence option D is correct